Customer Satisfaction Of Rail Transport Users Is Reviewed Through Services, Facilities And Ticket Prices - Rizkiana Karmelia Shaura; Hendra Kurniawan (Jurnal Mantik, 2022)
The purpose of this research is to identify the effect of services, facilities and ticket prices on train customer satisfaction at DAOP 2 Bandung. This research uses primary information in the form of a questionnaire filled out by respondents who have used local or long-distance train services. In collecting information, several respondents were selected from various kinds, so that the results given were representative. In the research, there were 31 respondents with various backgrounds. The procedure for analyzing information in this research uses the procedure for multiple linear regression analysis using the SPSS application. In light of the consequences of estimations utilizing the SPSS 26 application, the outcomes acquired that the help, offices and ticket costs affect consumer loyalty. Changed R square of 0.732 shows that 73.2% of the fluctuation or buyer fulfillment is clarified by the free factors in the relapse condition. Then again, 26.8% is clarified by different factors outside this exploration